Statistical analysis on the effect of exchange rate on stock price in Indonesia: an application of ARDL and IGARCH models. Issue 1 (May 2021) - Adam, P; Cahyono, E; Mukhsar,; Millia, H; Abapihi, B; Mukhtar, N; Ome, Lilis La
Abstract: This study aimed to examine the influence of the IDR/USD exchange rate on stock prices in Indonesia. The data used were the IDR/USD exchange rate and the monthly composite price index that spanned from January 2004 to October 2017. To test the effect of the IDR/USD exchange rate on stock prices, the distributed lag (ARDL) autoregressive model and integrated general autoregressive conditional heteroskedasticity (IGARCH) were used. The result of analysis showed that there was influence of IDR/USD rate to stock prices either in short term and in long term. In the long term, every 1% decrease in the exchange rate of IDR/USD, the change in stock price rise.